(untitled) (TAMADDUN NURI JURNALI, 2024)
This article focuses on the fact that the inclusion of active games in the educational process of young children helps to solve a number of special problems with high efficiency, as well as increase their interest in sports activities. The use of active games as a method and exercise in the learning process from an early age gives high results, and also plays an important role in increasing their motor activity.